The longest psalm: day-by-day responses to divine self-revelation - Casey, Michael (Liturgical Press, 2023)
"As the longest Psalm in the Bible, Psalm 119 comprises 176 verses. In The Longest Psalm, Michael Casey offers a meditative reading of each verse of the psalm to facilitate a truly personal expression of prayer and reflection. Each verse stands alone, intended to be read slowly, like the litanies familiar to Catholic devotion. Through this reflection, readers will discover the text is not merely a psalm to be sung but also a path to be followed"--